Advertising from the perspective of festivals: the present and future of commercial communication in the categories of awards (2013-2014) - Berlanga Fernández, Inmaculada; Galmés Cerezo, María; Victoria Mas, Juan Salvador (Comunication and Society, 2017)
Since the very beginning of research on the structure of the advertising system, advertising awards and acknowledgements have been referred to as one of its essential elements. In the specialised sector, a particular interest in advertising festivals has been acknowledged which tends to mirror the continuous evolution of the commercial communication system. With a clear interaction, festivals are forums in which professionals find suitable inspiration which has an impact on what is suggested by each festival each year for future ones. Hence, they become benchmarks for the present and future. Specifically, in order to show the latter aspect, this paper focuses on the organization of festivals and shows the major present and future advertising trends. In advertising, five major macro trends are addressed (Digitisation, New Alternatives, Innovation, Integration and Results) and following the results of our research, they are all covered in the festival awards. Specifically, according to the way the categories of advertising awards are presented, we have concluded that the digitisation of communications has come to an end; the "new ways" of communication in advertising are very present in all contests as the result of the current marketing communication campaigns in which new ways of communication are gradually gaining a more relevant role; innovation is essentially an advertising value; the context of integrated marketing communications is inherent to current advertising; and the effectiveness and results in festivals are significant.
Keywords: commercial communication system; advertising structure; advertising awards; advertising trends; Scopus; Emerging